2020
DOI: 10.1002/hsr2.179
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of schizophrenia and bipolar disorder individuals to make autonomous decisions about pharmacological treatments for their illness in real life: A scoping review

Abstract: Background and aim Having decision making capacity is central to the exercise of autonomy in mental health care. The objective of this scoping review is to summarize the evidence on the capacity of people with schizophrenia or bipolar disorder to make decisions about their treatment in real life to support medical practice. Methods Systematic search of observational studies on the assessment of capacity of patients with schizophrenia, psychosis, or bipolar disorder to make healthcare and treatment‐related deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
1
5
0
1
Order By: Relevance
“…These findings are consistent with adult populations showing that most adults with mental disorders retain decisional capacity ( Spencer et al, 2017 ), and that people with psychotic disorders are more likely to experience impaired decisional capacity than individuals with non-psychotic disorders ( Boettger et al, 2015 ; Owen et al, 2009 ). As in the current study, some studies demonstrated no relationship between age and decisional capacity among adults with psychotic disorders ( Palmer and Jeste, 2006 ; Pons et al, 2020 ), yet others have found greater capacity in younger individuals ( Pons et al, 2020 ). Prior research regarding the relationship between symptom severity and decisional capacity among adults with psychotic disorders has yielded inconsistent results.…”
Section: Discussionsupporting
confidence: 52%
“…These findings are consistent with adult populations showing that most adults with mental disorders retain decisional capacity ( Spencer et al, 2017 ), and that people with psychotic disorders are more likely to experience impaired decisional capacity than individuals with non-psychotic disorders ( Boettger et al, 2015 ; Owen et al, 2009 ). As in the current study, some studies demonstrated no relationship between age and decisional capacity among adults with psychotic disorders ( Palmer and Jeste, 2006 ; Pons et al, 2020 ), yet others have found greater capacity in younger individuals ( Pons et al, 2020 ). Prior research regarding the relationship between symptom severity and decisional capacity among adults with psychotic disorders has yielded inconsistent results.…”
Section: Discussionsupporting
confidence: 52%
“…In the presence of psychiatric comorbidity, the decisionmaking capacity to consent is rarely affected, but can be in some severe cases (43). Best practices of capacity to consent to treatment include considering variations in capacity over time and depending on the type of decision, the severity of symptoms, and the phase of the mental illness (44). Consequently, although every assessor has to feel competent to assess capacity, any overestimation of that competence could potentially and to some extent result in lack of recognition of individuals without capacity or missed opportunity to ask for a specialized advise, such as to a consultation-liaison psychiatrist when complexity arise from cases (45).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, all participants in this survey agreed that, in general, schizophrenia and bipolar disorder patients living in the community have the capacity to make decisions about their everyday healthcare and on the pharmacological treatment of their disease. Likewise, other authors have reported that psychiatric patients are capable of making treatment-related decisions, even when being admitted into hospital with considerable burden of symptoms [5,6,32]. In a systematic literature review, Hostiuc et al (2018) concluded that even in those circumstances in which schizophrenia patients are considered to have a significantly decreased decision-making capacity compared to non-mentally ill patients, they should be considered competent unless very severe changes are identifiable during clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly challenging for schizophrenia and bipolar disorder patients, where impaired insight and cognitive performance may further decrease their decision-making capacity [3,4]. In consequence, their decision-making capacity varies over time and with the type of decision to be made [3,5]. Several studies reveal that schizophrenia and bipolar disorder patients retain the capacity to make treatment and other healthcare-related decisions despite impairments at some stages of the illness, and this can be fully recovered after treatment [6].…”
Section: Introductionmentioning
confidence: 99%